Time Lapse to Colorectal Cancer: Telomere Dynamics Define the Malignant Potential of Polyps. Issue 9 (September 2016) - Druliner, Brooke R; Ruan, Xiaoyang; Johnson, Ruth; Grill, Diane; O'Brien, Daniel; Lai, Tsung‐Po; Rashtak, Shahrooz; Felmlee‐Devine, Donna; Washechek‐Aletto, Jill; Malykh, Andrei; Smyrk, Thomas; Oberg, Ann; et al.
Abstract : OBJECTIVE: : Whereas few adenomas become cancer, most colorectal cancers arise from adenomas. Telomere length is a recognized biomarker in multiple cancers, and telomere maintenance mechanisms (TMM) are exploited by malignant cells. We sought to determine whether telomere length and TMM distinguish cancer‐associated adenomas from those that are cancer‐free. METHODS: : Tissues were identified as cancer‐adjacent polyp (CAP)—residual adenoma contiguous with cancer—and cancer‐free polyp (CFP)—adenomas without malignancy. Telomere length, TMM, and expression were measured in 102 tissues including peripheral blood leukocytes (PBLs), normal colon epithelium, adenoma, and cancer (in CAP cases) from 31 patients. Telomere length was measured in a separate cohort of 342 PBL from CAP and CFP patients. RESULTS: : The mean differences in telomere length between normal and adenoma were greater in CAP than in CFP cases, P =0.001; telomere length in PBL was 91.7 bp greater in CAP than in CFP, P =0.007. Each 100 bp telomere increase was associated with a 1.14 (1.04–1.26) increased odds of being a CAP, P =0.0063. The polyp tissue from CAP patients had shorter telomeres and higher Telomerase reverse transcriptase (hTERT) expression compared with polyps from CFP patients, P =0.05. There was a greater degree of alternative lengthening of telomere (ALT) level difference in CFP polyps than in CAP polyps. The polyp telomere lengths of aggressive CAPs were significantly different from the polyps of non‐aggressive CAPs, P =0.01. CONCLUSIONS: : Adenomas that progress to cancer exhibit distinct telomere length and TMM profiles. We report for the first time that PBL telomeres differ in patients with polyps that become malignant, and therefore may have clinical value in adenoma risk assessment and management.